Benign Arylations of Dimethyl Itaconate via Heck–Matsuda Reaction Utilizing in‐Situ Generated Palladium on Aluminum Oxide. Issue 1 (3rd January 2020) - Matelienė (née Dauksaîtė), Lauryna; Knaup, Jan; von Horsten, Frank; Gu, Xiaoting; Brunner, Heiko
Abstract : In situ generated palladium on aluminum oxide provides an active and efficient catalytic system for the preparation of arylmethylidene succinates using the Heck–Matsuda reaction. Beside the monoarylation the first examples of the biarylation of these monomers will be described. Abstract : In situ generated palladium on aluminium oxide provides an active and efficient catalytic system for the preparation of arylmethylidene succinates using the Heck–Matsuda reaction. Beside the monoarylation the first examples of the biarylation of this monomer will be described.